Morphological, Molecular, and Morphometric Analysis of Aphelenchoides besseyi on Organic Rice (Oryza sativa) Seeds in the Beringin District, Deli Serdang Regency, Indonesia - Suswati, Suswati; Azwana, Azwana; Candra, Ifan Aulia; Kuniawati, Fitrianingrum; Siregar, Khofifah Muhaimini; Hasanah, Asmaul; Nasution, Aldy Elvanandar (UI Scholars Hub, 2025)
Aphelenchoides besseyi, a nematode, can infect rice resulting in the white shoot disease, which decreases the germina-tion rate and even causes seedling death. A. besseyi has recently been reported to mainly attack the organic rice varie-ties especially Pandanwangi and Ciherang in the Pasar Kawat, Beringin District, Deli Serdang, Indonesia. This research investigated A. besseyi via morphological, molecular, and morphometric approaches. The nematodes were observed in an area of 2000 m2, divided into five sample plots each with an area of 400 m2 on which Pandan Wangi and Ciherang rice were cultivated. Nematode morphology was observed using a stereo microscope at a 10–100x magnification. Mo-lecular identification employed PCR, followed by sequencing and phylogenetic analysis. This nematode possessed typ-ical morphological characteristics namely a longer female body (457.07–738.86 µm) than males (385.23–505.29 µm), and cured spicules, 17 to 21 µm long. The tail was ribbon-shaped with a tapered tip that had a mucrone with 2–4 points. Sequencing and phylogenetic analysis revealed that A. besseyi isolated from Indonesia (Deli Serdang/North Sumatra) was closely related to those from China, India, Russia, Taiwan, and Portugal with a 98% homology level.